Learning mind : experience into art - Jacob, Mary Jane.; Baas, Jacquelynn, 1948- (Chicago, Ill. : School of the Art Institute of Chicago ; Berkeley : University of California Press, 2009)
Introduction / Mary Jane Jacob and Jacquelynn Baas ##- On the being of being an artist : The gap between art and life / Arthur C. Danto ##- What art is and what artists do / Jerry Saltz ##- Multiple personalities : a how-to manual for artists and other creative types / Marcia Tucker ##- Meditation as art/art as meditation : thoughts on the relationship of non-intention to the creative process / Mark Epstein ##- Our barefoot practice / Ernesto Pujol ##- Making not knowing / Ann Hamilton ##- Fate and art / Magdalena Abakanowicz ##- It is difficult / Alfredo Jaar ##- Radical agency, massive change : social agendas in art and design / Kerry James Marshall and Bruce Mau with Lisa Wainwright ##- On making art and pedagogy : Teaching discourse : reflection strong, not theory light / Mika Hannula ##- Practicing Rauschenberg / Lisa Wainwright ##- Pedagogy, art, and the rules of the game / David J. Getsy ##- Zones of activity : from the gallery to the classroom / Ute Meta Bauer ##- Toward a new critical pedagogy / Lawrence Rinder ##- Fail again, fail better / Ronald Jones ##- Coming back to our senses / Alice Waters in conversation with Walter Hood ##- On experiencing art : Being with Cloud gate / Mary Jane Jacob ##- This is nowhere / Christopher Bedford ##- The look of the artist / Michael Brenson ##- Headless/heedless : experiencing Agora / W.J.T. Mitchell ##- Unframing experience / Jacquelynn Baas ##- The unknown child : art mediation/mediation art / Ulrich Schötker ##- Looking at an exhibition / Ronen Eidelman, Oǧuz Tatari, and Carolyn Bernstein ##- The empty conversation / Jacquelynn Baas, Mary Jane Jacob, and Ulrich Schötker.Introduction / Mary Jane Jacob and Jacquelynn Baas ##- On the being of being an artist : The gap between art and life / Arthur C. Danto ##- What art is and what artists do / Jerry Saltz ##- Multiple personalities: a how-to manual for artists and other creative types / Marcia Tucker ##- Medit
Includes bibliographical references and index.
boek